ANALISIS KUALITAS PELAYANAN PT TASPEN (PERSERO) DILIHAT DARI PERSEPSI PESERTA - Eko Andryanto Prakasa (Widyariset, 2009)
This Study aims to measure factors which have dominant influences to service quality of PT TASPEN (Persero)'s members. Further more it is used as a recommendations for PT TASPENs managerial to give an effective and efficient services. The perceptions of PT TASPEN's member was defined by five service dimensions (Parasuraman, 2005) - Reliability, Responsiveness, Assurance, Empathy, and Tangibility. This study used confirmatory factor estimated by weight least square method as a tool and LISREL 8.50 as the software. The data collected by survey using questionnaire. Sample size for this research is 855 respondents. And the result from this research is all dimension can reflect service quality of PT TASPEN (Persero). Assurance and responsiveness dimension have dominant factor in service quality in PT TASPEN (Persero). The company should give more attention to tangibility dimension to improve service quality.